Penerapan Sistem Pencatatan Kas Berbasis Akuntansi Keuangan Untuk Meningkatkan Kredibilitas UMKM Teh Solo Daerah Cengkareng: Implementation of Financial Accounting-Based Cash Recording System to Increase the Credibility of Solo Tea MSMEs in the Cengkareng Area - Salwa Habibah Natasya; Kamilatun Nufus; Chintya Ramayanti; Fadhiatul Billgiz; Ridha Ayu Artiyadi (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
This study aims to determine the implementation of a financial accounting-based cash recording system to enhance the credibility of Solo tea MSMEs in the Cengkareng area. Data collection methods were conducted through interviews, including one with Mrs. Tuti Henni as the owner of the Es Teh Solo business. The results indicate that financial management in the Es Teh Solo business has not yet run optimally, as the business owner has not consistently recorded daily transactions. The main obstacle identified is the low competence and understanding of basic accounting concepts and applicable financial reporting standards, which are heavily influenced by educational background. Although the business owner realizes the importance of financial statements, they still face significant challenges in implementation. Therefore, assistance programs and continuous financial literacy improvement are required to enhance the practical skills of Es Teh Solo business owners. Through this education, it is expected that business owners can prepare structured financial statements to support sustainable business management, planning, and growth in an optimal and efficient manner.